Assessment of E?ect of Hyperuricemia on Hearing Function - Shivam Aggarwal (Asian Journal of Medical Research, 2021)
Background: The aim is to assess the effect of on hearing function. Subjects and Methods: Eighty- six adults in age ranged 18-40 years of either gender with (Group I) and equal number of #8209; and #8209;matched normal individuals as controls (Group II) were enrolled. All patients were subjected to pure tone and distortion product and transient evoked ( and ) testing. Results: The mean TEOAE S/N ratio at 1 on right side was 8.43 and 8.40 and on left side was 8.24 and 8.35, at 2 on right side was 9.12 and 9.14 and on left side was 9.14 and 9.36, at 3 on right side was 5.54 and 9.02 and on left side was 5.30 and 10.4 and at 4 on right side was 1.81 and 9.4 and on left side was 1.62 and 7.6 respectively. The mean DPOAE S/N ratio at 3 on right side was 13.5 and 13.2 and on left side was 13.8 and 13.9, at 4 on right side was 16.5 and 17.0 and on left side was 15.2 and 15.1, at 5 on right side was 8.93and 14.3 and on left side was 8.71 and 14.1, at 6 on right side was 5.6 and 9.0 and on leftside was 4.3 and 10.2 respectively. The mean TEOAE value in right ear having > 3years and <3 years of duration of at 1 was 8.51 and 7.52, at 2 was 8.31 and 8.73, at 3 was 7.35 and 3.62 and at 4 was 2.52 and 1.45 respectively. The mean TEOAE value in left ear having > 3years and <3 years of duration of at 1 was 8.72 and 8.11, at 2 was 8.91 and 9.01, at 3KHz was 7.62 and 3.62 and at 4 was 1.74 and 1.23 respectively. Conclusion: It is found that increases the chances of hearing loss at high frequencies.